Dampak dari Customer Orientation of Employee dan Customer Participation pada Relationship Satisfaction: Peran Mediasi dari Customer Value - Sahara Sahara (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
The purpose of this paper is to seek to examine the role of mediation Customer Value (CV) the relationship between customer orientation of service employee (COSE) Customer Participation (CP) and Relationship Satisfaction (RS) the organization of public health services, hospital in West Java. The sample uses the respondent hospital patients in the disease amounted to 180 respondents. Structural equation modeling and confirmatory factor analysis was performed to evaluate hypothetical model. The size of the reliability and validity were also examined. Findings: Statistical analysis showed that following each COSE, and CP have a positive impact on CV, and CV increase RS. The practical implication: In the context of the health care industry at a hospital in West Java, Indonesia, the study offers a deeper understanding of the factors that influence CV, and how it affects RS CV. This understanding will help practitioners and policy formulating effective marketing strategies and strengthening services to customers on the basis of an interactive service on the front lines. The concierge service at the core and the spearhead in service in order to improve customer satisfaction by delivering high customer value.